Hybrid Methodology for Predicting Hypertension in Patients with Dyslipidemia and Type 2 Diabetes Mellitus - Mohamad Nasarudin Adnan; Wan Muhamad Amir W Ahmad; Farah Muna Mohamad Ghazali; Nor Azlida Aleng; Mohamad Shafiq Mohd Ibrahim; Nurfadhlina Abdul Halim (Pushpa Publishing House, 2025)
Indexed by WOS/Scopus/ERA